Case of Rhinosinusitis with Secondary Orbital Cellulitis Complicating further as Cavernous Sinus Thrombosis: A Rare Sequelae (GAIMS Journal of Medical Sciences, 2024)
Background: Orbital cellulitis is an acute inflammatory disorder of the orbit. It results from an acute infection spread from the blood, adjacent sinuses and facial skin. Cavernous sinus thrombosis (CST) typically occurs due to an infection originating from regions such as the face, sphenoid and ethmoid sinuses, or the oral cavity.Case report: An eleven-year-old girl was brought by her parents to our hospital with a complaint of right nasal discharge and fever for the last 10 days. She developed right-sided periorbital oedema for the past six days. She was under treatment at a local hospital. After that her parents noticed an increase in swelling associated with redness in her right peri-orbital region, so she came to our hospital. MRI brain showed changes of cavernous sinus thrombosis. A functional endoscopic sinus surgery (FESS) was performed for right nasal blockage on the second day of admission and about 10 ml of pus was drained. Fragmented fibrovascular tissue bits received from the frontal sinus and maxillary sinus revealed numerous pus cells with Gram-positive bacterial cocci on the third day. She responded to treatment as she was without fever by the day fourth on admission. The aerobic culture of the pus swab was positive and the organism detected was staphylococcus aureus on the eighth day after admission.Conclusion: Cavernous sinus thrombosis is a serious complication of orbital cellulitis with high morbidity and mortality. Unusually, orbital cellulitis occurs as sequelae of cavernous sinus thrombosis. Gram-positive bacteria noted on the nasal lesion's histopathology helped in starting antibiotics in the patient before the culture report was positive.